Ancient apocalypse death of the Nile - Page, Cynthia; British Broadcasting Corporation ([S.l.] : BBC Active, 2006)
In this video, the astronomers, geologists, archeologists and climatologists chart extraordinary discoveries and reveal new evidencd on ancient civilization. The Sphinx and mighty pyramids of Gaza are the only lasting evidence of a once-great civilization
Title from ttle screen
Executive producer, Alan Bookbinder ; photography, Nigel Meakin ; sound recordist, John Pritchard
Narrator: Hermione Norris
Keywords: Egypt -- Civilization; Egypt -- Social life and customs